Peningkatan Hasil Belajar melalui Model PBL Materi Struktur Bumi Kelas VII SMPN 1 Dayeuhluhur - Emon Sutarman; Alimin Alimin; Martiningsih Martiningsih (Universitas Negeri Makassar, 2022)
The implementation of the research by applying the Problem Based Learning (PBL) model is an effort to improve student learning outcomes. Learning by applying the lecture method that has been used so far causes problems where students are less active during the learning process. Research activities were carried out at SMP Negeri 1 Dayeuhluhur starting from July 31, 2021 until July 13, 2021. Activities carried out during the Research such as preparing the Learning Implementation Plan (RPP), compiling teaching materials, compiling media, compiling student worksheets, compiling questions and assessment instruments. The research conducted consisted of 2 cycles. Cycle I as many as 5 students achieved minimum completeness or 27% of the 18 students who attended. Cycle II as many as 9 students achieved minimum completeness or 50% of the 18 students who attended. So it can be concluded that the application of the Problem Based Learning (PBL) model can improve student learning outcomes of SMP Negeri 1 Dayeuhluhur.